2015
DOI: 10.5489/cuaj.2545
|View full text |Cite
|
Sign up to set email alerts
|

Serum follicle-stimulating hormone levels predict time to development of castration resistant prostate cancer

Abstract: This retrospective, single-centre study would suggest there may be an association between serum FSH levels and time to CRPC for men treated palliatively with ADT for advancing prostate cancer. Further clinical investigation in a larger cohort of men is required to determine any clinical utility of FSH as a biomarker of progression or target for therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 27 publications
0
19
0
Order By: Relevance
“…Fig 1 shows the procedure of literature search and study selection. The studies consisted of five RCTs [ 12 16 ], one prospective [ 19 ] and four retrospective cohort studies [ 17 , 18 , 20 , 21 ]. Basic characteristics, such as age, sex ratio, stone size and stone side, were described comparable between rigid URSL and PCNL group in each study and the data was presented in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Fig 1 shows the procedure of literature search and study selection. The studies consisted of five RCTs [ 12 16 ], one prospective [ 19 ] and four retrospective cohort studies [ 17 , 18 , 20 , 21 ]. Basic characteristics, such as age, sex ratio, stone size and stone side, were described comparable between rigid URSL and PCNL group in each study and the data was presented in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Basic characteristics, such as age, sex ratio, stone size and stone side, were described comparable between rigid URSL and PCNL group in each study and the data was presented in Table 1 . Some studies also reported other basic characteristics that might make a difference in the clinical outcomes: preoperative renal function including serum creatinine (SCr), blood urea nitrogen (BUN) or golomeruar filtration rate (GFR), failed SWL history, and degree of hydronephrosis [ 14 , 15 , 17 , 19 , 20 ]. All the data was also comparable between the two groups according to each study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…24 Studies have shown correlations between serum FSH and the pathological stage of prostate cancer 23 and, more recently, time to castration resistant prostate cancer in a retrospective analysis. 25 …”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies detected overexpression of FSH receptors in prostate cancer compared to benign prostatic epithelium [ 60 ]. Moreover, a FSH value more than the lowest tertile (>4.8 mIU/mL) may be associated with shorter time to CRPC progression [ 61 ]. Taken together, the efficacy of GnRH antagonists may be due to lack of FSH stimulation as opposed to GnRH agonists.…”
Section: Introductionmentioning
confidence: 99%